Crafting the Future of Poetry in Schools: Developing Contextual-Based Think, Talk and Write Worksheets for Primary School Students - Firman; Suryani, Lilis; Malagunna, Filda Angriani (Educational Journal of Learning Technology, 2023)
Teaching materials play an important role in the success of the learning process. However, the lack of variety in teaching materials can reduce student interest. This study developed an innovative LKPD with a think-talk write model based on contextual material for writing poetry in class IV SDN 011 Rante Pasang. The Research and Development approach with the ADDIE model is used. The validity and practicality of LKPD were tested with very good validity (80.33%) and usefulness (students: 90.61%, educators: 92.85%). This product meets the needs of students, facilitates understanding, and increases interest and motivation in learning.